Governing fables : learning from public sector narratives - Borins, Sandford F., 1949- (Research in public management (Unnumbered), 2011)
Governing Fables: Learning from Public Sector Narratives advocates the importance of narrative for public servants, exemplifies it with a rigorously selected and analyzed set of narratives, and imparts narrative skills politicians and public servants need in their careers. Governing Fables turns to narratology, the inter-disciplinary study of narrative, for a conceptual framework that is applied to a set of narratives engaging life within public organizations, focusing on works produced during the last twenty-five years in the US and UK. The genres discussed include British government narratives inspired by and reacting to Yes Minister, British appeasement narratives, American political narratives, the Cuban Missile Crisis narrative, jury decision-making narratives, and heroic teacher narratives. In each genre lessons are presented regarding both effective management and essential narrative skills.Governing Fables is intended for public management and political science scholars and practitioners interested in leadership and management, as well as readers drawn to the political subject matter and to the genre of political films, novels, and television series.